A Metamaterial Route to Realize Acoustic Insulation and Anisotropic Electromagnetic Manipulation Simultaneously. Issue 8 (13th July 2018) - Zhang, Cheng; Song, Gang Yong; Ma, Hui Feng; Yang, Jin; Cao, Wen Kang; Xie, Xian You; Chen, Ping; Cheng, Qiang; Wu, Li Ting; Cui, Tie Jun
Abstract: Recently, artificially structured metamaterials (MMs) are proposed to manipulate the wave propagation behaviors in single physical domain. However, the multiphysics manipulation is rarely reported and remains a challenging issue to be investigated. Here, the design of MMs with simultaneous controls of acoustic and electromagnetic (EM) waves is presented. A double‐membrane structure is proposed to meet the need of acoustic‐wave insulation, and patterned anisotropic meta‐atoms on the membrane are employed to generate polarization‐dependent functions of EM waves. The designed structure is validated numerically and experimentally, suggesting a new route for joint modulations of acoustic and EM waves in the engineering. Abstract : The design of metamaterials with simultaneous controls of acoustic and electromagnetic waves is presented. A double‐membrane structure is proposed to achieve acoustic‐wave insulation, and patterned anisotropic meta‐atoms on the membrane are employed to generate polarization‐dependent electromagnetic waves. This structure is validated numerically and experimentally, suggesting a new route for joint modulations of acoustic and electromagnetic waves in the engineering.